2022
DOI: 10.14814/phy2.15253
|View full text |Cite
|
Sign up to set email alerts
|

Transcutaneous auricular vagus nerve stimulation augments postprandial inhibition of ghrelin

Abstract: Vagus nerve stimulation (VNS) facilitates weight loss in animals and patients treated with VNS for depression or epilepsy. Likewise, chronic transcutaneous auricular VNS (taVNS) reduces weight gain and improves glucose tolerance in Zucker diabetic fatty rats. If these metabolic effects of taVNS observed in rats translate to humans is unknown. Therefore, the hypothesis of this study was that acute application of taVNS affects glucotropic and orexigenic hormones which could potentially facilitate weight loss and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 63 publications
0
8
0
Order By: Relevance
“…An important factor that might modulate the effectiveness of taVNS in regulating cardiovascular function is the body's metabolic state (Kozorosky et al, 2022;Sclocco et al, 2019;Szulczewski, 2022). After the caloric load, we found that taVNS decreased HF-HRV and RMSSD further amplifying the reduction in RMSSD and HF-HRV induced by the milkshake.…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…An important factor that might modulate the effectiveness of taVNS in regulating cardiovascular function is the body's metabolic state (Kozorosky et al, 2022;Sclocco et al, 2019;Szulczewski, 2022). After the caloric load, we found that taVNS decreased HF-HRV and RMSSD further amplifying the reduction in RMSSD and HF-HRV induced by the milkshake.…”
Section: Discussionmentioning
confidence: 76%
“…In addition, small sample sizes (Wolf et al, 2021, meta-analysis: median(N) = 30, range(N) = 7-60 of taVNS studies with within-subject design), lack of a common stimulation protocol, appropriate baseline measurements, and adequate control conditions may contribute to discrepancies across studies. Likewise, other physiological factors, such as the respiratory rate or hormonal balance (Kozorosky et al, 2022;Sclocco et al, 2019;Szulczewski, 2022), interact with the effect of taVNS, indicating a complex interplay between physiological states and taVNS-induced changes. To summarize, pressing questions about the differential effects of taVNS at the left vs. the right ear and the emerging evidence of interactions with metabolic state (Altınkaya et al, 2023;Vosseler et al, 2020) call for additional studies on cardiovascular effects.…”
Section: Introductionmentioning
confidence: 99%
“…35 One key aspect of patient selection relates to recent discoveries that VNS has a myriad of effects—systemically and neurologically—which are only now becoming apparent. In addition to VNS′ well-documented and U. S. Food and Drug Administration–approved indication for depression, 36 early reports document therapeutic benefit in seemingly unrelated and comorbid disorders in patients with epilepsy including autism spectrum disorder, 37 obesity, 38 heart failure, 39 and rheumatoid arthritis. 40 As our understanding of the role of VNS in these and other disorders evolves, it will be important to consider these factors as well when identifying surgical candidates for VNS implantation.…”
Section: Discussionmentioning
confidence: 99%
“…VNS, vagus nerve stimulation; FDA, Food and Drug Administration; COVID-19, coronavirus disease 2019; ns, non-significant effect on study measure outcome. Reference number , 1 (Addorisio et al, 2019 ), 2 (Arsava et al, 2022 ), 3 (Badran et al, 2020 ), 4 (Chang et al, 2021 ), 5 (Courties et al, 2022 ), 6 (Dawson et al, 2021 ), 7 (De Ridder et al, 2015 ), 8 (Diener et al, 2019 ), 9 (Fisher et al, 2016 ), 10 (Garcia et al, 2021 ), 11 (Gaul et al, 2016 ), 12 (Gazi et al, 2022 ), 13 (Genovese et al, 2020 ), 14 (George et al, 2005 ), 15 (George et al, 2008 ), 16 (Goadsby et al, 2018 ), 17 (Gomolka et al, 2018 ), 18 (Grazzi et al, 2017 ), 19 (Kawai et al, 2017 ), 20 (Kozorosky et al, 2022 ), 21 (Kreuzer et al, 2014 ), 22 (Labar et al, 1999 ), 23 (Lange et al, 2011 ), 24 (Manning et al, 2019 ), 25 (Merchant et al, 2022 ), 26 (Mertens et al, 2022 ), 27 (Morris et al, 2013 ), 28 (Morris and Mueller, 1999 ), 29 (Muthulingam et al, 2021 ), 30 (Najib et al, 2022 ), 31 (Paccione et al, 2022 ), 32 (Redgrave et al, 2018 ), 33 (Rush et al, 2005a ), 34 (Rush et al, 2005b ), 35 (Salama et al, 2020 ), 36 (Shi et al, 2021 ), 37 (Silberstein et al, 2016a ), 38 (Silberstein et al, 2016b ), 39 (Stavrakis et al, 2020 ), 40 (Tassorelli et al, 2018 ), 41 (Tirado et al, 2022 ), 42 (Tornero et al, 2022 ), 43 (Tyler et al, 2017 ), 44 (Verrier et al, 2016 ), and 45 (Wittbrodt et al, 2021 ).…”
Section: Clinical Implications Of Vnsmentioning
confidence: 99%